QTL mapping and improvement of pre-harvest sprouting resistance using japonica weedy rice - Lee, Chang-Min; Park, Hyun-Su; Baek, Man-Kee; Jeong, O-Young; Seo, Jeonghwan; Kim, Suk-Man (Frontiers in Plant Science, 2023)
The stability of cultivation and production in terms of crop yield has been threatened by climate change due to global warming. Pre-harvest sprouting (PHS) is a threat to crops, especially staple foods, including rice, because of reductions in yield and quality. To address the problem of precocious germination before harvest, we performed quantitative trait loci (QTL) analysis for PHS using F8 RILs populations derived from japonica weedy rice in Korea. QTL analysis revealed that two stable QTLs, qPH7 and qPH2, associated with PHS resistance were identified on chromosomes 7 and 2, respectively, explaining approximately 38% of the phenotypic variation. The QTL effect in the tested lines significantly decreased the degree of PHS, based on the number of QTLs included. Through fine mapping for main QTL qPH7, the region for the PHS was found to be anchored within 23.575–23.785 Mbp on chromosome 7 using 13 cleaved amplified sequence (CAPS) markers. Among 15 open reading frames (ORFs) within the detected region, one ORF, Os07g0584366, exhibited upregulated expression in the resistant donor, which was approximately nine times higher than that of susceptible japonica cultivars under PHS-inducing conditions. Japonica lines with QTLs related to PHS resistance were developed to improve the characteristics of PHS and design practical PCR-based DNA markers for marker-assisted backcrosses of many other PHS-susceptible japonica cultivars.